Spatial distribution and correlates of smoking in Zambia - Herbert Tato Nyirenda; David Mulenga; Moono Silitongo; Herbert BC Nyirenda; Tambulani Nyirenda (BMJ Open)
Objective The objective of the paper was to investigate the spatial distribution and correlates of tobacco smoking in various regions of Zambia.Methods This paper adopts a cross-sectional study design. The study used data from the 2013/2014 Zambia Demographic Health Survey which is a nationwide health survey conducted in all the 10 provinces. A random sample of men and women from 15 920 households was successfully selected and interviewed. All women aged 15–49 and men aged 15–59 who were either permanent residents of the households or visitors present in the households on the night before the survey were eligible to be interviewed.Results The results show that 8.2% and 11% of Zambians in urban and rural areas smoke, respectively. In urban areas, the risk of being a cigarette smoker was 2.31 (CI: 1.69 to 3.16) and 2.03 (CI: 1.36 to 3.02) times higher for the divorced and separated. However, the risk of being a cigarette smoker was lower for those with some formal education. In rural areas, the risk of being a cigarette smoker was lower for the married (relative risk ratios (RRR): 0.69, CI: 0.55 to 0.86) and those with a formal education. Nevertheless, in rural areas, the risk of being a pipe and other smoker was higher for those who were self-employed (RRR: 8.46, CI: 2.95 to 24.20) and with an occupation (RRR: 2.37, CI: 1.39 to 4.02) but was lower among women.Conclusion Tobacco smoking varies between and within regions as well as provinces. Therefore, interventions to curb smoking should target specific demographic, socioeconomic and cultural factors and how they are spatially distributed.